Evaluation of the soil microbiome of three raised beaches in the Devon Island Lowland, High Arctic, Canada - Laura Maretto; Saptarathi Deb; Andrea Squartini; Giuseppe Concheri; Piergiorgio Stevanato; Serenella Nardi; Stefania Cocco; Giuseppe Corti (PLoS ONE, 2025)
The Arctic region is characterized by severe temperatures and a unique ecosystem with largely unexplored microbiomes. Whereas soil microbiomes in temperate regions play key roles in nutrient cycling, organic matter decomposition, greenhouse gas fluxes, and overall ecosystem functioning, Arctic microbiomes remain poorly understood, highlighting the need for a thorough characterization to better predict and manage soil health and resilience. In this study, we compared the microbial profiles of three raised beaches on Devon Island (Nunavut, Canadian Arctic Archipelago), which emerged sequentially between eight and two thousand years ago, to assess their similarities and differences. Samples were collected by genetic horizons along excavations from the top layer to the permafrost. For each horizon, total soil DNA, 16S gene copies dPCR quantification, 16S metabarcoding, and functional prediction were carried out. Total DNA quantification revealed a consistently comparable concentration of genetic material across the three soil beaches (AB2 μ = 2.28 ± 5.44 μg ∙ g -1 , AB1 μ = 4.71 ± 2.35 μg ∙ g -1 , AB3 μ = 5.44 ± 2.91 μg ∙ g -1 ), regardless of site age (AB2 = 2,360 YBP, AB1 = 6,726 YBP, AB3 = 8,410 YBP). Conversely, clear differences emerged by comparing the different horizons at each site. The hierarchical cluster analysis based on the Bray-Curtis dissimilarity matrix revealed a clear separation between surface and deep horizons. The core microbiome analysis highlighted Actinobacteria, Proteobacteria, and Firmicutes as the three predominant phyla accounting for relative abundances of 42%, 22%, and 18%, respectively. Remarkable evidence was the unexpectedly high taxonomic diversity that was recorded in these sites and that surprisingly matched with the commonly observed values in soils of temperate regions. Since these stony shores developed under cold, life-limiting conditions, their apparent microbial richness raises doubts about the potential biases in inferring physiological contexts and active biodiversity directly inferred from culture-independent DNA-based studies. The reason is that such inventories can be possibly inflated, in all environments, by chronically accumulated cells from passive immigration events through atmospheric discharge.